Prediction of Ligand Transport along Hydrophobic Enzyme Nanochannels - Diego E. Escalante; Alptekin Aksan (Computational and Structural Biotechnology Journal, 2019)
Buried active sites of enzymes are connected to the bulk solvent through a network of hydrophobic channels. We developed a discretized model that can accurately predict ligand transport along hydrophobic channels up to six orders of magnitude faster than any other existing method. The non-dimensional nature of the model makes it applicable to any hydrophobic channel/ligand combination.